Assessment of hospital readiness for obstetric hemorrhage. Issue 2 (May 2015) - Lal, Ann K.; Geller, Stacie; Scott, Shirley; Hibbard, Judith U.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to evaluate the hospital readiness for obstetric hemorrhage before and after the implementation of obstetric hemorrhage education. Study design Retrospective analysis. Materials and methods In 2008–2009, the State of Illinois Obstetric Hemorrhage Education Project was implemented for providers involved in the care of pregnant women. A survey 'Management of Obstetric Hemorrhage: Hospital Assessment' was administered in 2006 before the project, and subsequently in 2010, after the project, to 133 total participating hospitals that delivered obstetric care. Survey information included questions on response times for laboratory values and blood products as well information on response time for special personnel required in obstetric hemorrhage. χ2-Test and t-test were used to compare the presurvey and postsurvey results. Results A total of 120 hospitals completed both surveys. Overall, there was an increase in the availability of obstetric providers in the hospital 24 h a day after implementation of the project. The length of time to obtain STAT laboratory results and time to receive blood products decreased significantly from 2006 to 2010. There were increases in the number of hospitals that had obstetric personnel, both physicians and nursing staff, participate in obstetric hemorrhage drills, up from 23–44% to 99% in 2010. In addition, 23% of hospitals had policies on identifying and assessing at-risk women in 2006, which increased to 80% in 2010. Conclusion The implementation of hemorrhage education resulted in increased preparedness of hospitals to diagnose and treat obstetric hemorrhage as indicated by an improvement in blood product response time and availability of necessary supplies.